Kenya Food Systems Conference, April 5-6, 2023 - CGIAR (CGIAR System Organization, 2023)
This playlist is a collection of two videos recorded on April 5-6, 2023, at the Kenya Food Systems Conference at Safari Park Hotel, Nairobi, Kenya. Organized by the Ministry of Agriculture and Livestock Development (MoALD) and the CGIAR Initiative on National Policies and Strategies (NPS), it had two key aims: to come up with a set of recommendations to guide food system transformation policies over the coming years and work out how to enhance the dialogue between scientists and policymakers.